A legitimidade para agir do Ministério Público de Contas no direito brasileiro - Silva, Rildo Vieira da (2009)
This work is the result of a study which aims to show the legitimacy and postulated judicial capacity of the Ministry of Public Accounts. An institution that received constitutional treatment only through the Charter of the Republic, 05.10.1988, its functions are governed in a scattered way throughout the body of the Constitution, including its own powers of prosecutors that correlates with the raw power of the Court of Accounts. The first chapter is devoted to the Court of Auditors in Brazil - its origins, historical development, the legal nature of their decisions and institutional competence. In the second chapter, emphasis is given to the origin of the Ministry of Public Accounts and their legal position in the Brazilian legal system as well as the prerogatives and prohibitions imposed on its members. The third chapter turns to the study of the phenomenon of legitimacy in the plans of the General Theory of law and procedural law. The last chapter is devoted to the study of Public Prosecution Policy as a subject of special process and the Ministry of Public Accounts as a legitimate agent to promote the implementation of the instrument from the decision of the Court which imposes a debt or fine.